Determinants Of CGPI Score - Handoyo, Sigit; Salihah, Riadhani (Future : Jurnal Manajemen dan Akuntansi, 2018)
The objective of this research is to find out the influence of firm size, profitability, leverage, growth, regulation factor and unqualified audit opinion toward Corporate Governance Perception Index (CGPI) score. There are 94 samples of data used in this study. The sample size is obtained from companies that are listed in CGPI and Indonesian Stock Exchange (IDX) during 2007 ? 2012. The result from this study shows that firm size and profitability and unqualified audit opinion have positive significance influence to corporate governance perception index (CGPI) score. Meanwhile, leverage, growth and regulation factor have positive insignificance influence to corporate governance perception index (CGPI) score.